Convallatoxin Promotes M2 Macrophage Polarization to Attenuate Atherosclerosis Through PPARγ-Integrin αvβ5 Signaling Pathway - Zhang Y; Shi X; Han J; Peng W; Fang Z; Zhou Y; Xu X; Lin J; Xiao F; Zhao L; Lin Y (Dove Medical Press, 2021)
Yi Zhang,1 Xiujin Shi,1 Jialun Han,1 Wenxing Peng,1 Zhenwei Fang,1 Yang Zhou,1 Xiaoyu Xu,1 Jie Lin,2,3 Fucheng Xiao,4 Limin Zhao,3 Yang Lin1 1Department of Pharmacy, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China; 2Department of Endocrinology and Metabolism, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China; 3Department of Atherosclerosis, Beijing Institute of Heart, Lung and Blood Vessel Diseases, Beijing, 100029, People’s Republic of China; 4Department of Cardiovascular Surgery, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of ChinaCorrespondence: Yang LinDepartment of Pharmacy, Beijing Anzhen Hospital, Capital Medical University, No. 2 Anzhen Road, Beijing, 100029, People’s Republic of ChinaTel/Fax +86-10-64456045Email linyang3623@outlook.comIntroduction: As the primary immune cells, macrophages play a key role in atherosclerotic progression. M2 macrophage polarization has been reported to promote tissue repair and attenuate plaque formation upon the expression of anti-inflammatory factors. Convallatoxin (CNT) is a natural cardiac glycoside with anti-inflammatory pharmacological properties. However, whether CNT protects against atherosclerosis (AS) and underlying mechanisms is unknown. This work was designed to explore the potential effects of CNT on atherosclerosis.Methods: In this study, Apolipoprotein E deficiency (ApoE−/-) mice fed with high-fat diet were established, and CNT (50 or 100 μg/kg) were intragastrically administrated for 12 weeks every day. In vitro, RAW264.7 macrophages stimulated with ox-LDL were treated with CNT (50 or 100 nM) for 24 h. The specific PPARγ antagonist, GW9662, was used to block the PPARγ signaling pathway in vitro. Then, the atherosclerotic lesions, macrophage polarization markers, inflammatory cytokines and PPARγ signaling pathway were examined in further examinations.Results: Our results showed that the atherosclerotic lesions were reduced by CNT, as demonstrated by the downregulation of serum lipid level and aortic plaque area in AS mice. Furthermore, we found that CNT treatment promoted the expression of M2 macrophage markers (Arg1, Mrc1, Retnla and Chi3l3), and decreased the levels of pro-inflammatory cytokines (IL-6 and TNF-α), accompanied by the increase of anti-inflammatory factor (IL-10) in aortic vessels of AS mice. In ox-LDL-induced RAW264.7 cells, CNT administration also facilitated macrophages polarizing towards M2 subtype and inhibited inflammatory responses. Furthermore, both the in vivo and in vitro experiments showed CNT could increase the expression of PPARγ, Integrin αv and Integrin β5, and GW9662 could block CNT-induced M2 macrophage polarization.Conclusion: Taken together, these data suggest that CNT may promote M2 macrophage polarization to exert an anti-atherosclerotic effect, partially through activating PPARγ-Integrin αvβ5 signaling pathway.Keywords: atherosclerosis, convallatoxin, macrophage polarization, ox-LDL, PPARγ-Integrin αvβ5 signaling pathway